Breakthrough Cancer Pain Is Associated with Spinal Gap Junction Activation via Regulation of Connexin 43 in a Mouse Model - Li, Xin; Jiang, Siqing; Yang, Hui; Liao, Qian; Cao, Shousong; Yan, Xuebin; Huang, Dong (Frontiers in Cellular Neuroscience, 2017)
Breakthrough cancer pain (BTcP) is a high-intensity, short-duration, unpredictable and uncontrollable pain. Recent studies have shown that activation of gap junction (GJ) in spinal cord plays an important role in the pathogenesis of BTcP. We examined the expressions of Glial fibrillary acidic protein (GFAP), connexin (Cx) 43 protein and phosphorylation of Cx43 (p-Cx43) in the spinal cord of mice. In addition, we investigated the effects of Gap26, a selective GJ blocker, on the expressions of GFAP, Cx43, and p-Cx43 in BTcP mice. We found that the expressions of GFAP and Cx43 proteins were significantly upregulated while p-Cx43 was down-regulated in the spinal cord in a mouse model of BTcP. The overexpression of Cx43 protein in the spinal cord increased GJ formation and enhanced BTcP. The variation of the ratio of p-Cx43/T-Cx43 (total Cx43) affected the function of GJ to induce BTcP. Furthermore, BTcP was alleviated by Gap26 via reducing pain hypersensitivity. The inhibition of Cx43 and p-Cx43 by Gap26 attenuated BTcP but the p/T ratio of Cx43 remained unchanged in BTcP mice. We reveal that the expression and phosphorylation of Cx43 affected BTcP and GJ activation facilitated BTcP via a Cx43-mediated signaling in the spinal cord. The finding may provide a scientific rationale for discovery and development of novel therapeutic targets for the treatment of BTcP clinically.